Children Friendly School as the Legal Protection for Children in Indonesia - Ratri Novita Erdianti; Sholahuddin Al-Fatih (Varia Justicia, 2020)
The large number of child abuse rates in the school environment forces the government to make policies to tackle it. Through child-friendly schools, it will provide protection for children in educational units. Furthermore, this paper aims to give a solution through child-friendly school. Not only creating schools that are safe from violence, but child-friendly schools also provide opportunities for children to carry out enjoyable learning processes and strengthen children's character. Child friendly schools have provided legal protection for children's rights while in the education unit. Through a child friendly school program based on the principles of child protection and prioritizing the fulfillment of children's rights, it will be a solution for the government today in dealing with various forms of violence that occur in schools.